Characteristics of initial symptoms in patients with dementia with Lewy body disease - Fei, Min; Wang, Fei; Wu, Hao; Liu, Shuai; Gan, Jinghuan; Ji, Yong (Frontiers in Neurology, 2022)
Background：Dementia with Lewy bodies (DLB) is the second most common neurodegenerative dementia. Although DLB is characterized by fluctuating cognitive impairment, somes symptoms may appear before cognitive impairment, including rapid eye movement sleep behaviour disorder (RBD), psychiatric symptoms， autonomic symptoms and parkinson's symptoms, etc.Therefore, DLB may be misdiagnosed as other diseases in the early stage. Objective: The purpose of this study was to investigate the characteristics of initial symptoms of DLB,which potentially could supply important clues to the earliest diagnosis of this disorder. Methods：A total of 239 patients with probable DLB who visited the cognitive impairment outpatient department of Tianjin Huanhu Hospital from September 2015 to March 2021 were consecutively enrolled. We retrospectively evaluated the initial symptoms of all included participants. The time of onset of initial symptoms was also assessed. Results: The most frequent initial symptom was memory loss (53.9%), followed by psychiatric symptoms(34.7%), RBD(20.9%), parkinsonism (15.1%) and autonomic symptoms (10.1%). There was a significant gender and age differences in initial symptoms of patients with DLB. Conclusions：Our study elucidated the initial symptoms in patients with probable DLB. RBD was significantly more reported by men than women, whereas women showed a higher incidence of visual and auditory hallucinations. A better understanding of the initial symptoms of DLB could lead to a more accurate diagnosis.